Good University Governance Dan Kinerja-Pt: Model Pemetaan Dan Perancangan Kinerja-Pt Melalui Kualitas & Kompetensi Lulusan, Pelayanan Serta Daya Saing Menuju Kualitas Lulusan Dan World Class University - Pratolo, Suryo; Jatmiko, Bambang; Manuhara, Wahyu (Akmenika, 2015)
The purpose of this research is to build Mapping Patterns and Good Design and Performance-PT: Quality and Graduate Competency, Services and competitiveness towards quality graduates and World Class University. Basing a common phenomenon that attempts Universities to wards international reputation in the fields of science, technology and art as mandated in the vision and mission of the University, should be managed seriously, education and research, and community service to build a shared commitment in supporting the quality of human resources in all areas in a sustainable manner. The problem in this research is low competitiveness of Indonesian state human resources is one of the nations major problems that require action immediately. According to data from the World Economic Forum, Indonesias competitiveness in 2013-2014 was ranked 38th out of 148 countries surveyed. Factors that affect the competitiveness of a nation is a community education. Research methods, using a survey method approach: pre-survey, observation, data used is secondary data, with the Forum Group Discussion. The results of the study all University at 5 Kopertis already mapped well, but not all integrated based on IT-Web (80%) means that the leadership commitment needs to be improved. Researchers have carried out the design of IT-Web and will be implemented in year 2 (two).